2017
DOI: 10.1038/cddis.2017.362
|View full text |Cite
|
Sign up to set email alerts
|

Adropin deficiency worsens HFD-induced metabolic defects

Abstract: The limited efficacy of current treatment methods and increased type 2 diabetes mellitus (T2DM) incidence constitute an incentive for investigating how metabolic homeostasis is maintained, to improve treatment efficacy and identify novel treatment methods. We analyzed a three-generation family of Chinese origin with the common feature of T2DM attacks and fatty pancreas (FP), alongside 19 unrelated patients with FP and 58 cases with T2DM for genetic variations in Enho, serum adropin, and relative Treg amounts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 39 publications
1
50
0
1
Order By: Relevance
“…Downregulation of adropin in circulation in type 2 diabetes was also reported by Chen et al [24]. These patients, who also have fatty pancreases, have lower serum levels of adropin [24]. It is also important to note that patients with lower adropin levels show a Cys56Trp mutation in the Enho gene [24].…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 59%
See 2 more Smart Citations
“…Downregulation of adropin in circulation in type 2 diabetes was also reported by Chen et al [24]. These patients, who also have fatty pancreases, have lower serum levels of adropin [24]. It is also important to note that patients with lower adropin levels show a Cys56Trp mutation in the Enho gene [24].…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 59%
“…In addition, low levels of adropin in type 2 diabetes mellitus are a risk factor for endothelial dysfunction [23]. Downregulation of adropin in circulation in type 2 diabetes was also reported by Chen et al [24]. These patients, who also have fatty pancreases, have lower serum levels of adropin [24].…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, the decrease of Treg cells in adipose tissue also leads to the occurrence of insulin resistance, so it is believed that Treg cells play an important role in metabolic regulation [20,21]. Additionally, a previous research reported that adropin deficiency associates with loss of Treg cells and leads to autoimmune diseases [22].…”
Section: Metabolic Disorders Caused By the Immune Regulation Of Adropinmentioning
confidence: 99%
“…With regulation of the phenotype of macrophages, it exerts proinflammatory or anti-inflammatory effects on atherosclerosis. In terms of energy metabolism, metabolic disorders caused by insulin resistance or inflammation leads to activations of inflammatory transcription factor nuclear factor kB (NF-κB) and inflammatory signaling system, as well as elevated levels of cytokines, thereby accelerating the damage to function of endothelial cells and formation of atherosclerotic plaques [22]. As a regulator of energy metabolism, adropin may exert its potential anti-inflammatory effects through regulation of energy metabolism.…”
Section: Correlation Between Inhibition Of Inflammation By Adropin Anmentioning
confidence: 99%